Optimization of Double Bottom Design in Cargo Hold Areas: Case Study Of Tanker With Lengths 150 m and Above - Raybonda Reinaldi Winarko; Berlian Arswendo Adietya; Andi Trimulyono; Sunardi Sunardi; Stefanus Eko Wiratno; Ardiansyah Musa Efendi; Ardi Nugroho Yulianto (Department of Naval Architecture - Diponegoro University, 2026)
The shipping industry is keep advancing to produce the most efficient ship designs, including tanker ship designs. According to MARPOL Annex 1 Regulation 19, oil tankers with a deadweight of over 600 tonnes and built after 6 July 1996 must have double side and double bottom structures. These structures are intended to prevent oil spill in the event of hull damaged. However, they significantly reduce the cargo hold volume. Therefore, the objective of this research is to optimize the cargo hold volume by optimizing the double bottom design along the cargo oil tank. One of the optimization methods that can solve this problem is the brute force search method. Unlike heuristic algorithms, it provides exact rather than approximate results, making it ideal for solving small-scale problems with shorter iteration times. In this research, the variables are the locations of two cargo landing points at each knuckle of the ship's cargo oil tank. The constraints are the regulations governing clearance, stability, freeboard, and longitudinal strength of ship. The research resulted in a new design that increased the cargo oil tank volume by 375.996 m³, equivalent to 0.865%. A new ship with the same payload can be constructed using an optimized cargo oil tank configuration, reducing both the cargo tank length and the overall ship length by 1.011 m.